2010
DOI: 10.1007/s00384-010-1065-8
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy affects staging of colorectal liver metastasis—a comparison of PET, CT and intraoperative ultrasound

Abstract: Staging accuracy of colorectal liver metastasis is influenced by neoadjuvant chemotherapy. For PET, decreased tumour metabolism rather than downsizing may account for a drop in sensitivity after neoadjuvant chemotherapy. IUS is critical to avoid incomplete resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
19
0
2
Order By: Relevance
“…It is well known that chemotherapy-related changes result in a significant decline in the diagnostic performance of postchemotherapy imaging, especially for CT and PET [12,13,28]. Similarly, we originally expected that the diagnostic performance of gadoxetic acid-enhanced MRI would decline somewhat following chemotherapy, since sinusoidal injury may impair the detection of small focal liver lesions on MRI by hiding the lesion or leading to a false-positive lesion as a result of the typical diffuse reticular hypointensity seen on the HBP image [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that chemotherapy-related changes result in a significant decline in the diagnostic performance of postchemotherapy imaging, especially for CT and PET [12,13,28]. Similarly, we originally expected that the diagnostic performance of gadoxetic acid-enhanced MRI would decline somewhat following chemotherapy, since sinusoidal injury may impair the detection of small focal liver lesions on MRI by hiding the lesion or leading to a false-positive lesion as a result of the typical diffuse reticular hypointensity seen on the HBP image [27].…”
Section: Discussionmentioning
confidence: 99%
“…This has also been shown to have a clear influence on the staging accuracy of preoperative imaging modalities for CRLMs [11][12][13][14]. In a recent metaanalysis study by van Kessel et al [15], CT, FDG-PET and FDG-PET/CT showed lower diagnostic performances for the evaluation of CRLMs in patients treated with chemotherapy compared to chemonaive patients, whereas MRI showed a high pooled sensitivity of 85.7 % in patients who underwent chemotherapy.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, the use of chemotherapy less than 1 month before the scan can result in high false negative results [10,11]. In these cases, ceCT has been demonstrated to be superior to the PET to correctly evaluate liver metastases after neadjuvant chemotherapy [12].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the use of chemotherapy less than 1 month before the scan can result in high false negative results [12]. In these cases, ceCT has been demonstrated to be superior to the PET to correctly evaluate liver metastases after neadjuvant chemotherapy [13].…”
Section: Recommendations For Contrast Enhanced Computed Tomography/pomentioning
confidence: 99%